Digital media law - Packard, Ashley (John Wiley & Sons, Inc., 2013)
Covering the latest legal updates and rulings, the second edition of Digital Media Law presents a comprehensive introduction to all the critical issues surrounding media law. Provides a solid foundation in media lawIllustrates how digitization and globalization are constantly shifting the legal landscapeUtilizes current and relevant examples to illustrate key conceptsRevised section on legal research covers how and where to find the lawUpdated with new rulings relating to corporate political speech, student speech, indecency and Net neutrality.